VCD PLAYER SEBAGAI MEDIAPEMBELAJARAN GEOMETRI UNTUK SISWAKELAS VIII SMPN 2 BANTUL YOGYAKARTA - Sriyono, Fitriyani, Haryani, Nur Hadi (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
Video Compact Disk (VCD) is an electronic tool which is easily found at affordableprice. In addition to the entertainment function, this tool can be used to support thelearning process. This research aims to know the effectivity of VCD player as thegeometry-learning media for the students of junior high school and the interest of thesestudents toward VCD player as learning media.The subject of this experimental research was the students of class VIII SMPN 2Bantul, involving three groups; 1) Group A for the students who had not got VCDplayer 2) group B for the ones who had got VCD player but not be monitored, and 3)group C for the ones who had got VCD player and were monitored. The instruments ofthis research were 1) questionnaire for people responsible for a pupil, 2) interestquestionnaire 3) pre-test and pos-test, and 4) evaluation questionnaire. The materialsdelivered in the learning CD was space structure. The materials were packed up in theform of audio-visual.The result of the research reveals that VCD player is effective to be used as geometrylearningmedia for the students of class VIII SMP 2 Bantul Yogyakarta, and the use ofVCD player in learning geometry can improve the students’ interest to this subject.Key words: Video Compact Disk (VCD), Geometry, SMP